2013
DOI: 10.4067/s0717-65382013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Selección denso-dependiente de microhabitat en Galaxias platei: un estudio experimental

Abstract: RESUMENGalaxias platei es la especie nativa de mayor distribución en la Patagonia Chilena, habitando ambientes fl uviales y principalmente lacustres. Utiliza variados hábitats, desde plataformas de arcilla consolidada a ambientes de sustrato fi no y otros con presencia de macrófi tas, vegetación leñosa o sustrato rocoso grueso. En este trabajo analizamos experimentalmente la selección de microhábitat de G. platei y su dependencia con la disponibilidad de refugio y la densidad de peces que lo utilizan. Para ell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Salmonid density in Patagonian lakes has been found to be negatively correlated with trophic level in G. platei of piscivorous body length (Correa et al, 2012), but no specimens of this size were caught in the San Pedro River. Laboratory studies have concluded that native galaxiids show some tendencies towards anti-predatory behaviour (Sobenes et al, 2013b), including increased swimming activity and reduced oxygen consumption but not including enhanced use of refugia in the presence of nonnative predators (Milano et al, 2010;Sobenes, 2013a). It is therefore unclear how much of the apparent segregation shown in the MRTs is as a result of predation, interference, predator avoidance or divergent habitat preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonid density in Patagonian lakes has been found to be negatively correlated with trophic level in G. platei of piscivorous body length (Correa et al, 2012), but no specimens of this size were caught in the San Pedro River. Laboratory studies have concluded that native galaxiids show some tendencies towards anti-predatory behaviour (Sobenes et al, 2013b), including increased swimming activity and reduced oxygen consumption but not including enhanced use of refugia in the presence of nonnative predators (Milano et al, 2010;Sobenes, 2013a). It is therefore unclear how much of the apparent segregation shown in the MRTs is as a result of predation, interference, predator avoidance or divergent habitat preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Ordination showed that the mesohabitats of each bank had similar environmental characteristics, supporting the latter hypothesis. Furthermore, the low swimming capacity of many native species would render them vulnerable to isolation because of the width of the channel and the higher velocities found along the thalweg (García et al, 2012b;Sobenes et al, 2013b). More research into the swimming capacity and dispersal behaviour of these species is required in order to evaluate these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…An initial population size of n ¼ 100 000 was chosen as this is the expected maximum size of a G. platei population inhabiting a lake with an area of 10 000 m 2 (i.e. maximum expected density: 10 individuals m 22 ; [44]). We thus simulated a typical G. platei population inhabiting a salmonid-free lake.…”
Section: (D) Simulationsmentioning
confidence: 99%
“…The 0% and 90% levels of population size reduction represented 2 extreme scenarios. For these analyses, we used the present genotypic data, a carrying capacity of 500 individuals/km 2 , as suggested for G. platei populations from Chile (Sobenes et al 2013), mean fecundity of 20,000 (Zama 1986), and parameters detailed in Supporting Information.…”
Section: Simulations Of Future Populationsmentioning
confidence: 99%